Patient‐reported outcomes among patients with type 2 diabetes mellitus treated with dapagliflozin in a triple‐therapy regimen for 52 weeks. Issue 3 (5th January 2016) - Grandy, S.; Sternhufvud, C.; Ryden, A.; Sugg, J.; Rohwedder, K.
Abstract : Patients with type 2 diabetes (T2DM) and inadequate glycaemic control on combination metformin (MET) and sulphonylurea (SU) were enrolled in a 24‐week, double‐blind, randomized, placebo‐controlled study with a 28‐week extension. The five‐dimension EuroQol questionnaire (EQ‐5D), SHIELD Weight Questionnaire‐9 (WQ‐9), Impact of Weight on Quality of Life‐Lite (IWQOL‐Lite) questionnaire and the Diabetes Treatment Satisfaction Questionnaire (DTSQ) were used to evaluate health status and health‐related quality of life (HRQoL) at baseline and week 52. Patients with dapagliflozin 10 mg + MET + SU (n = 108) were compared with patients treated with placebo + MET + SU (n = 108), using a repeated‐measures mixed model. EQ‐5D visual analogue scale scores, IWQOL‐Lite and DTSQ scores improved in the dapagliflozin and placebo groups from baseline to week 52; however, there was no significant difference between groups (p > 0.20). EQ‐5D index scores remained the same from baseline to week 52 for dapagliflozin and placebo (p = 0.54). A numerically greater proportion of the dapagliflozin group reported improvement in all nine SHIELD WQ‐9 items compared with placebo, and the difference was statistically significant for physical health (p = 0.017). Over 52 weeks of therapy, patients maintained their health status and HRQoL when dapagliflozin was added to the treatment.